Use of Ultrasonography to Locate Laryngeal Structures for Laryngeal Electromyography. Issue 6 (18th November 2013) - Seo, Han Gil; Jang, Hye Jin; Oh, Byung‐Mo; Kim, Won; Han, Tai Ryoon
Abstract : Objective: To measure the representative anatomic landmarks for laryngeal electromyography (LEMG) and to delineate an accurate ultrasonography‐guided approach. Design: A retrospective study. Setting: A university hospital. Participants: A total of 518 patients (270 men and 248 women) who underwent LEMG. Methods: The medical records, LEMG records, and ultrasonographic measurements of the patients who underwent LEMG in our electromyography laboratory between March 2010 and January 2013 were reviewed. Main Outcome Measurement: The longest dimension of the cricothyroid membrane, the height of the arch of the cricoid cartilage, and the distance from the superior border of the cricoid cartilage to the midpoint of the vocal fold were measured by using ultrasonography. Results: A total of 585 studies in 518 patients with a standard deviation (SD) mean age of 56.01 ± 14.36 years (men, 59.28 ± 14.09 years; women, 52.45 ± 13.81 years) were reviewed. The most common etiology was surgery (44.6%), and the left side (56%) of the vocal folds was more frequently involved than the right side (23.4%) or both sides (9.4%). The longest dimension of the cricothyroid membrane, height of the arch of the cricoid cartilage, and distance from the superior border of the cricoid cartilage to the midpoint of the vocal fold measured 1.06 ± 0.33 cm (men, 1.16 ± 0.34 cm; women, 0.97 ± 0.29 cm), 0.83 ± 0.24 cm (men, 0.88 ± 0.24 cm; women, 0.77 ± 23 cm), and 1.88 ± 0.48 cm (men, 2.09 ± 0.51 cm; women, 1.70 ± 0.36 cm), respectively. All measurements differed significantly between the men and women ( P < .001 by Student t test). Conclusions: The current study provides reference ranges for ultrasonographic measurements of important anatomic landmarks for LEMG. This study also provides a technique for using ultrasonography in LEMG. Ultrasonography may be used as an adjuvant to overcome certain technical pitfalls of LEMG.